Cytotoxicity and antioxidant activity of plant extracts from Vietnam - Mai Phuong, Nguyen Thi; Boger, Christin; Ulrike, Lindequist (Academia Journal of Biology, 2020)
Traditional medicine plays an important role in treatment of human diseases. Extracts from medicinal plants exhibit many valuable biological activities. However, the exploitation and application of the extracts requires knowlege on the mechanism of action. In this study, cytotoxic and antioxidant activites of the methanol and hexane extracts of 09 Vietnamese plants have been studied in vitro on keratinocyte HaCaT cell line. The results showed that all plant extracts had a cytotoxyc effect on HaCaT cells. The hexane extracts showed more potent than the methanol extract. Garcinia mangostana exhibited the best cytotoxicity with IC50 values of 14.42 mg/ml (for hexane extract) và 14.27 mg/ml (for MeOH extract). All tested extracts resulted in the generation of intracellular reactive oxygen radicals in HaCaT cells. Mangifera indica, Cleistocalyx operculatus and Terminalia catappa had the best DPPH radical scavenging activity with EC50 values of 23.0 mg/ml, 27.4 mg/ml and 23.73 mg/ml, respectively. Besides, G. mangostana and T.catappa exhibited capacity of eliminating active oxygen radicals (iROS). The test extracts significantly reduced the number of cells in phase G1 and increased the number of cells in S and G2/M phases. The data obtained in this study are the preliminary results for further studies on the mechanisms of action and therapeutic applications of these plants.